Optimization of Behavioral Segmentation-Based Omnichannel Strategies in Managing the Student Journey Experience at Private Universities in Indonesia: A Conceptual Review - Muhammad Ardiansyah; Muhammad Amir Anshori (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The increasing reliance of students on both digital and physical channels necessitates private universities to manage interactions and services in a more integrated and cohesive manner. An omnichannel strategy represents a relevant approach; however, its implementation in higher education institutions remains largely partial and predominantly focused on marketing communication. As a result, it has yet to effectively manage the student journey experience in a comprehensive manner. This study aims to develop a conceptual framework for optimizing omnichannel strategies based on student behavioral segmentation in managing the student journey experience at private universities in Indonesia. Employing a qualitative approach, this research adopts a narrative literature review guided by PRISMA principles, examining scholarly publications from the past five years indexed in the Scopus and SINTA databases. The findings indicate that omnichannel integration lacking a behavioral understanding of students tends to produce experiences that are generic, fragmented, and unsustainable. This study concludes that behavioral segmentation should be positioned as a fundamental basis for strategic decision-making in omnichannel management, enabling the design of contextual and consistent student experiences across all stages of the academic journey. The implications of this research provide a conceptual foundation for universities to develop adaptive, cross-channel integrated student experience management systems that support the sustainability of long-term relationships between institutions and students.